A Comparative Study of the Results of the Anatomic Medial Portal and All-inside Arthroscopic Acl Reconstruction - KUMAR SHANTANU; SUDHIR SHYAM KUSHWAHA; DEEPAK KUMAR; VINEET KUMAR; SHAILENDRA SINGH; VINEET SHARMA (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Many techniques of graft placement in Arthroscopic Anterior Cruciate Ligament (ACL) reconstruction is available nowa-days, like trans-tibial, anatomical accessory medial portal and anatomical all-inside technique. Aim: To compare the improvement in clinical status of patients treated by anatomic accessory medial portal and all-inside arthroscopic ACL reconstruction technique pre-operatively postoperatively using International Knee Documentation Comittee (IKDC) Subjective Knee Scores, Lysholm Knee Score, Knee Society Score, Lachman test, Visual Analog Score (VAS) in both the groups. Materials and Methods: After informed consent from patients and clearance from Ethical Committee, we included patients aged 18 to 50 years with ACL injury and clinical laxity admitted in Department of Orthopaedics, King George Medical University, Lucknow. We included 100 patients in the study, which were divided into two groups, Group1 comprised of patients treated by Anatomic accessory medial portal technique and group 2 comprised of patients treated by All-Inside technique. Then the patients were followed up post-operatively at 6 weeks, 12 weeks and 6 months, clinically for functional status using Lysholm Knee Score, IKDC Subjective Knee Score, Knee Society Score and VAS score. Grading of laxity was evaluated by Lachman test at preoperative stage and 6 months follow-up. After collection of the data, analysis was carried out on SPSS software version 16.0 (Chicago, inc. USA) and the statistical test that was used was 2-Way Analysis of Variance (ANOVA). Results: IKDC Subjective Knee Score, Lysholm Knee Score, Knee Society Score, Lachman Test and VAS Score was better in group 2 treated by All-inside technique as compared to group1 and the difference was significant (p<0.005). Conclusion: All- Inside arthroscopic ACL reconstruction technique (group2) is a better technique than arthroscopic Anatomic accessory medial portal technique (group1).